An Analysis Of Sense Based Sentence On Lyric Of Adele's Songs In The 19 And 21 Albums - Amalia, Renanda Rizky, Dra. Siti Zuhriah Ariatmi, M.Hum, Dr. Dwi Haryanti, M.Hum (2014)
This research belongs to qualitative research. The research purposes to identify the types of sense based sentence and illocutionary meaning or author‟s intention in the lyric of Adele‟s albums. This research is using scope of pragmatics to find out the author‟s intention. The objects of the research are lyrics in the Adele‟s album entitled 21 and 19 which consist of 21 songs. In collecting data, researcher uses the document. The data in this research are simple declarative sentences containing types of sense based sentence, they are analytic sentence, syntactic sentence, contradiction sentence and the illocutionary meaning or author‟s intentions, they are stating, informing, asserting, disclosing, offering, warning, threatening, affirming, promising, alleging, identifying, deploring, questioning, conjecturing, claiming and disputing. From the collected data, the researcher finds 50 data. The result of the research shows that: (a) There are three kinds of sense based sentences from 50 data found in Adele‟s album. They are analytic sentence (2 data/ 4,0%), syntactic sentence (29 data/ 58,0%) and contradiction sentence (19 data/ 38,0%). (b) There are 16 kinds of illocutionary meaning found in Adele‟s album. They are stating (5 data/10,0%), informing (21 data/ 42,0%), asserting (2 data/ 4,0%), disclosing (2 data/ 4,0%), offering(2 data/ 4,0%), warning(2 data/ 4,0%), threatening (2 data/ 4,0%), affirming (2 data/ 4,0%), promising (2 data/ 4,0%), alleging (1 datum/ 2,0%), identifying (1 datum/ 2,0%), deploring (4 data/ 8,0%), questioning (1 datum/ 2,0%), conjecturing (1 datum/ 2,0%), claiming (1 datum/ 2,0%) and disputing (1 datum/ 2,0%).